Production of biodiesel from palm fatty acid distillate by microwave-assisted sulfonated glucose acid catalyst - Nur Nazlina Saimon,; Heng, Khuan Eu; Anwar Johari,; Norzita Ngadi,; Mazura Jusoh,; Zaki Yamani Zakaria, (Penerbit Universiti Kebangsaan Malaysia, 2018)
Biodiesel, one of the renewable energy sources has gained attention for decades as the alternative fuel due to its remarkable properties. However, there are several drawbacks from the industrial production of biodiesel such as the spike in the production cost, environmental issues related to the usage of homogeneous catalyst and profitability in long term. One of the solutions to eliminate the problem is by utilizing low cost starting material such as palm fatty acid distillate (PFAD). PFAD is a byproduct from the refining of crude palm oil and abundantly available. Esterification of PFAD to biodiesel will be much easier with the presence of heterogeneous acid catalyst. Most of acid catalyst preparation involves series of heating process using conventional method. In this study, microwave was utilized in catalyst preparation, significantly reducing the reaction time from conventional heating method. The catalyst produced was characterized using X-Ray Diffraction (XRD), Brunauer Emmet and Teller (BET), Scanning Electron Microscopy (SEM), Temperature-Programmed Desorption - Ammonia (TPD-NH3) and Fourier Transform Infrared (FTIR) while percentage yield and conversion of the PFAD were analysed by gas chromatography - flame ionization detector (GC-FID) and acid-base titration, respectively. It has been demonstrated that the percentage yield of biodiesel from the PFAD by employing sulfonated glucose acid catalyst (SGAC) reached 98.23% under the following conditions: molar ratio of methanol to PFAD of 10:1, catalyst loading of 2.5% and reaction temperature of 70oC. The microwave-assisted SGAC showed its potential to replace the SGAC produced via conventional heating method.